The politics of influence : British ex-servicemen, Cabinet decisions and cultural change, 1917-57 - Wootton, Graham (Routledge, 1998)
First published in 1998.
Includes index.
Keywords: Veterans -- Great Britain.; Great Britain -- Politics and government -- 20th century.; Anciens combattants -- Grande-Bretagne.; Grande-Bretagne -- Politique et gouvernement -- 20e siècle.; HISTORY -- Military -- Other.; TECHNOLOGY & ENGINEERING -- Military Science.; Politics and government; Veterans; Great Britain; 1900-1999; Electronic book.